(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
In this article, the effect of planting dates on productive stalks and productive stems of new durum wheat varieties currently being planted in dry areas of our republic is highlighted, and recommendations are given on planting dates of new durum wheat varieties.